A Closer Look at the Potential Mechanisms of Action of Protective Agents Used in the Drying of Microorganisms: A Review - Charlotte Van Engeland; Benoît Haut; Frédéric Debaste (Microorganisms)
Yeast, bacteria and sourdough are widely used in our daily lives, yet their drying and storage remains a significant challenge. A variety of techniques are used to improve the resistance of cells to thermal, dehydration, oxidative and osmotic stresses, which can occur at different stages of the process. The addition of protective agents prior to drying is a commonly used method, but the mechanisms that may lead to a change in viability following the addition of these agents, or more generally, the interaction between a protective agent and the drying process, are not yet fully understood. This review outlines seven main potential mechanisms, as highlighted in the literature, which can lead to internal or external modifications of the cells. The mechanisms in question are change of membrane fluidity, accumulation of compounds for osmoregulation, prior osmotic dehydration, prevention of oxidation, coating or encapsulation, enhancement in thermal resistance and change in drying kinetics. A comprehensive explanation of these mechanisms is provided. This review also highlights the connection between the mechanisms and the influence of the stresses occurring during drying and storage, which depend on the drying technique used and the operating conditions, the strains and the protective agents involved, on the importance of the different protection mechanisms. By gaining a deeper understanding of the mechanisms of action of protective agents, strategies to improve the quality of the microorganisms obtained after drying can be developed. One such strategy would be to combine several agents to achieve a synergistic effect.